Białe certyfikaty jako instrument podnoszenia efektywności końcowego wykorzystania energii w Unii Europejskiej - Borys, Grażyna (White certificates as instruments for upgrading the efficiency of ultimate energy usage in the European Union, 2008)
The objective of the hereby article is the system of white certificates trading as instruments for upgrading the efficiency of ultimate energy usage. Poland goes through the preparation period for this system implementation. The study presents several suggestions referring to the system architecture which constitutes the author’s input into public discussion on working out solutions that could result in upgrading the effectiveness and efficiency of the said instrument.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 22, s. 23-32